RAISING ENGINEERING AND ECONOMIC FIGURES OF ELECTRIC STOVE IRON RINGS FOR CATERING ENTERPRISES - Vladimir P. Kirpichnikov; Artem M. Davydov; Denis M. Davydov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides analysis of the factors affecting service life of electric stove iron rings at catering enterprises. It is shown that temperature conditions of the ring working surface and the heating spiral depend seriously on the material of kitchen utensils and on the average air gap between the ring working surface and utensils’ bottom, whose value is measured as a result of temperature deforming of the ring working surface during heating. In order to diminish the value of average air gap between the ring and kitchen utensils in the process of food cooking it is proposed to treat mechanically the ring working surface during its manufacturing with fixed temperature conditions. Better adjoining of the utensils’ bottom to the ring working surface can lead to decreasing temperature on its working surface and thus, to optimization of the process of thermal treatment of food, which can increase service life of the ring and cut specific consumption of electric power per unit of cooked food.